2004
DOI: 10.1002/j.0022-0337.2004.68.1.tb03734.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Fissure Sealant Program as Part of Community‐Based Teaching and Training

Abstract: Since 1995 the Department of Community Dentistry of the University of Pretoria has been involved in the rendering of mobile primary oral health care services to children in the Hammanskraal area of Gauteng, South Africa, as part of their students' community-based training. Mokonyama Primary School was identified as the first school where a primary oral health care service could be rendered. The objective of this study was to evaluate the impact (outcomes) of a fissure sealant program on the dentition status of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…A 7‐year prospective cohort study, carried out in South Africa, observed that the DMFT of the school children who participated in the SBDS program was significantly lower than that of a comparable group of children from the same area who were not enrolled in the program. Unfortunately, the baseline differences concerning the fluoride content of the drinking water between the compared groups could have confounded the results, and the follow‐up was poorly described .…”
mentioning
confidence: 99%
“…A 7‐year prospective cohort study, carried out in South Africa, observed that the DMFT of the school children who participated in the SBDS program was significantly lower than that of a comparable group of children from the same area who were not enrolled in the program. Unfortunately, the baseline differences concerning the fluoride content of the drinking water between the compared groups could have confounded the results, and the follow‐up was poorly described .…”
mentioning
confidence: 99%
“…Similar sentiments were expressed in an evaluation of a mobile dental fissure sealant programme in Hammanskraal, South Africa. The authors attributed the low levels of uptake due to poor parental consent and absenteeism on days when the dental mobile was present at the school premises [ 18 ]. Similar challenges were experienced in the study conducted in Thailand [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, fissure sealants were found to cost less in terms of the procedures undertaken. Given that they are one of the priority prevention strategies recommended to reduce dental caries amongst school children in South Africa [ 18 ]. Scaling up the uptake of school mobile dental screening and fissure sealant programmes in the country could potentially result in a reducing dental caries in an efficient manner.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] A study conducted in Hammanskraal, an area in the Gauteng Province of South Africa with high natural fluoride levels in the water supply, revealed a 75.2% reduction in caries levels amongst 15 year-old children who had twice been treated with fissure sealants over a seven year period. 13 This study set out to examine the management of dental patients who suffered inherited bleeding disorders and to assess the protocols followed at WOHC and CMAH in comparison with international standards. The use of replacement therapy, alone and in combination with TA, was observed among the subjects who had undergone extractions, full mouth root planing with scaling and polishing, restorative, and endodontic procedures.…”
Section: < 503mentioning
confidence: 99%